2017
DOI: 10.17556/erziefd.299182
|View full text |Cite
|
Sign up to set email alerts
|

Üniversite Öğrencilerinde Bağlanma Stilleri ve Akademik Başarının Merhamet Üzerindeki Yordayıcı Etkisi

Abstract: This research aims to examine the predictive power of attachment styles (safe, fearful, obsessive, indifferent) and academic achievement averages on the compassion of university students. The study also examines whether university students show difference in terms of safe attachment style and compassion scores with their birth order and perceived parental attitudes. Erzincan University students who are studying in the spring semester of 2015-2016 academic year constitute the study's universe. The study sample … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 30 publications
(29 reference statements)
1
2
0
Order By: Relevance
“…The nurses in this study had a high compassion level. In the literature, some studies have reported similar results to the present study (Arlı et al 2018;Çingöl et al 2018;İşgör 2017;Meyer et al 2015;Büyük et al 2021;Karadağ et al 2018). In the study by Arkan (2020), nurses had a medium compassion level (Arkan et al 2020).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The nurses in this study had a high compassion level. In the literature, some studies have reported similar results to the present study (Arlı et al 2018;Çingöl et al 2018;İşgör 2017;Meyer et al 2015;Büyük et al 2021;Karadağ et al 2018). In the study by Arkan (2020), nurses had a medium compassion level (Arkan et al 2020).…”
Section: Discussionsupporting
confidence: 89%
“…Additionally, compassion enables nurses to establish therapeutic communication with patients and facilitates their ability to understand patients, recognize their emotions and needs and meet their spiritual needs (Uslu et al 2016). Studies indicated that nurses have high compassion levels (Arlı et al 2018;Büyük et al 2021;Çingöl et al 2018;İşgör 2017;Meyer et al 2015;Karadağ et al 2018). Compassionate care practices, which may be a quality indicator, increase patient satisfaction levels and comfort of care and make patients feel better (Çınar et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…In the studies of Sprecher and Fehr (2005), compassion is conceptualized as compassionate (sensitive) love. Compassionate (sensitive) love is defined as an attitude toward humanity that involves behavior, feeling and thinking that focuses on concern, caring and support for humanity, as well as a motivation to understand and help humanity when they are most in need (İşgör 2017b;Akdeniz and Deniz 2016).…”
Section: Introductionmentioning
confidence: 99%